Developing Student Worksheet Based on Islamic, Science, Environment, Technology, and Society on Junior High School Students' Critical Thinking Skills - Puspita, Laila; Rakhmawati, Ismi; komarudin, Komarudin (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
This research aims to develop I-SETS-based LKPD to train critical thinking skills of SMP/MTs students to train critical thinking skills of SMP/MTs students in biology learning. The type of research used is Research and Development (R&D) according to the ADDIE development steps (Analysis, Design, Development, Implementation, and Evaluation). The results of validation tests by language, religion, and media experts stated that the learning media was suitable for use, while material experts stated that the learning media was very suitable for use. The results of the students' attractiveness response test based on small group and large group trials obtained the criteria for interpreting students' responses, namely very interesting. Meanwhile, the results of the effectiveness test of I-SETS-based LKPD to train critical thinking skills of SMP/MTs students on animal and plant breeding material in the learning process could not be implemented due to COVID-19 which occurred globally throughout the world, including the learning process of students in school. So, this research and development is only carried out to the attractiveness response testing stage.ABSTRAK: Penelitian ini bertujuan untuk mengembangkan LKPD berbasis I-SETS untuk melatih keterampilan berpikir kritis siswa SMP/MTs untuk melatih keterampilan berpikir kritis siswa SMP/MTs pada pembelajaran biologi. Jenis penelitian yang digunakan yaitu Research and Development (R&D) menurut langkan pengembangan ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Hasil uji validasi oleh ahli bahasa, agama, dan ahli media menyatakan bahwa media pembelajaran layak digunakan, sedangkan untuk ahli materi menyatakan bahwa media pembelajaran sangat layak digunakan. Hasil uji respon kemenarikan siswa berdasarkan uji coba kelompok kecil dan kelompok besar memperoleh kriteria interpretasi respon siswa yaitu sangat menarik. Sedangkan hasil uji efektivitas LKPD berbasis I-SETS untuk melatih keterampilan berpikir kritis siswa SMP/MTs pada materi perkembangbiakan hewan dan tumbuhan dalam proses pembelajaran tidak dapat terlaksana dikarenakan adanya COVID-19 yang terjadi secara global diseluruh penjuru dunia, termasuk proses pembelajaran siswa di sekolah. Sehingga penelitian dan pengembangan ini hanya dilaksanakan sampai tahap uji respon kemenarikan saja.